Implementation and Analysis of k-Barrier Coverage in Wireless Sensor Networks - Anand, Anagha S; Anitha, V. S (International Journal of Computer Sciences and Engineering, 2018)
Coverage area regarding a particular sensor means the area that can be monitored using a sensor. Barrier coverage enhances the intrusion detection that can be done with a directional sensor. Omni-directional sensors senses the data surrounding it in all directions with a predefined boundary, whereas directional sensors are used to obtain data from a particular direction of area which will be the region of interest. Barrier coverage is a critical issue in most of the border security applications. This paper deals with the protocol used for the implementation of k-barrier coverage. k is a variable which is used to denote the number of times an intruders path is detected across the protected belt area. The region of interest will be highly protected when the value of k is high.